A recombinant live attenuated tetravalent vaccine for the prevention of dengue. (3rd July 2017) - Guy, Bruno; Noriega, Fernando; Ochiai, R. Leon; L'azou, Maïna; Delore, Valentine; Skipetrova, Anna; Verdier, François; Coudeville, Laurent; Savarino, Stephen; Jackson, Nicholas
ABSTRACT: Introduction : Dengue is an important and still growing public health problem associated with substantial morbidity, as well as significant social and economic impact. The present review describes the main features and development of the first dengue vaccine (CYD-TDV, Dengvaxia®), which has been licensed by several dengue-endemic countries in Asia and Latin America for use in populations above 9 years of age. Areas covered : The review focuses on the large clinical development of CYD-TDV, which includes in particular two pivotal phase III efficacy trials conducted in Asia and Latin America and supported vaccine licensure. Based on these clinical data, the WHO Strategic Advisory Group of Experts (SAGE) on Immunization recommended considering introduction of the vaccine in geographic settings (national or subnational) with high burden of disease. Long-term safety follow-up studies of the efficacy trials are currently ongoing, and post-licensure studies will evaluate the vaccine effectiveness and safety in 'real-life' following vaccine introduction. Expert commentary : During vaccine development, a number of complexities were tackled, innovation pursued, and risk managed. These aspects, as well as the potential impact of CYD-TDV on public health are also discussed.